2020
DOI: 10.1002/mc.23177
|View full text |Cite
|
Sign up to set email alerts
|

CPNE1 predicts poor prognosis and promotes tumorigenesis and radioresistance via the AKT singling pathway in triple‐negative breast cancer

Abstract: Elevated expression of Copine 1 (CPNE1) has been observed in multiple cancers; however, the underlying mechanisms by which it affects cancer cells are unclear. We aimed to study the effect of CPNE1 on the tumorigenesis and radioresistance of triple‐negative breast cancer (TNBC). Quantitative real‐time polymerase chain reaction was used to detect the expression of CPNE1 in TNBC tissues and cell lines. Western blot, immunohistochemistry, and immunofluorescence were used to investigate the levels of CPNE1, p‐AKT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…According to the latest American cancer statistics, breast cancer is estimated to be the most common cancer and the second most common cause of cancer-associated deaths in women [ 1 ]. Owing to higher distal metastatic and recurrent rates, triple-negative breast cancer (TNBC) patients exhibit worse overall and disease-free survival than any other type of breast cancer [ 2 4 ]. Etiology investigations suggest that hereditary factors account for nearly one-tenth of breast cancer cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the latest American cancer statistics, breast cancer is estimated to be the most common cancer and the second most common cause of cancer-associated deaths in women [ 1 ]. Owing to higher distal metastatic and recurrent rates, triple-negative breast cancer (TNBC) patients exhibit worse overall and disease-free survival than any other type of breast cancer [ 2 4 ]. Etiology investigations suggest that hereditary factors account for nearly one-tenth of breast cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…deaths in women [1]. Owing to higher distal metastatic and recurrent rates, triple-negative breast cancer (TNBC) patients exhibit worse overall and disease-free survival than any other type of breast cancer [2][3][4]. Etiology investigations suggest that hereditary factors account for nearly one-tenth of breast cancer cases.…”
mentioning
confidence: 99%
“…CPNE1 also regulates tumorigenesis and correlates with the survival of lung and prostate cancer patients. [7][8][9]24,25 However, its role in CRC is unclear. The present study showed that CPNE1 was overexpressed in CRC tissues and promoted CRC progression.…”
Section: Dovepressmentioning
confidence: 99%
“…TNBC is the BC subtype that is most aggressive and invasive. It accounts for approximately 15–20% of all breast cancer cases [ 3 ]. In comparison with other types of breast cancer, TNBC shows unfavorable prognostic features: increased frequency of visceral metastases, shorter interval without recurrence, and higher nuclear grade [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%